Influence of Axial Force in The Intermediate Shaft on the Load Capacity of the Paired Cardan Mechanism - Pavić, Branimir; Radoš, Jerko; Perše, Silvestar (Promet - Traffic&Transportation, 2012)
The design of intermediate shaft with axially movablesplined joint must be adapted to the variable position of theshaft axis, i.e. to the change of the joint angle during operation.This design is also used for the reduction of axial forces whichare caused by inaccuracy in the production and assembling ofC(ll·dan mechanisms. The axial force which is generated by frictionof contact swfaces in the splined joint is the function of themagnitude of the transfeJTed torsion moments, splined dimensions,lubrication conditions, and materials used for contactswfaces. It will cause additional bearing loads at cross journalsand in the shaft supports, as well as unallowed vibrations andnoise during operation, thus affecting the safety and lifetime ofthe Cardan mechanism. The theoretical and empirical analysisof Cm·dan mechanisms, which have been studied with andwithout axial forces in the splinedjoint and its effect on durabilityof mechanism elements have been presented.